Effectiveness of Law Number 2 of 2002 Concerning Police Members Who Commit Alleged Violations or Criminal Acts in the Case of Ferdy Sambo - Nuarsa, I Komang Gede; Paraniti, A.A. Sagung Poetri; Pidada, Ida Bagus Anggapurana (Journal of Progressive Law and Legal Studies, 2023)
The problems in this study are how the effectiveness of Law Number 2 of 2002 concerning the police for members who commit alleged violations or criminal acts and what are the obstacles in implementing Law Number 2 of 2002 concerning the police for members who commit alleged violations or criminal acts. The purpose of this research is to make a contribution, especially about the science of law so that function for know the effectiveness of Law Number 2 of 2002 concerning the police. This study uses a normative type of legal research, namely research by describing the facts examined and related to existing laws and regulations. The conclusion of this study is to find several violations or crimes that have been committed by the Indonesian police, including: Narcotics Abuse, Theft, and Discipline Violations. The effectiveness of Law Number 2 of 2002 concerning the Indonesian National Police in the case of premeditated murder involving Ferdy Sambo, et al helped to outline the parts that were violated such as Article 35 (1), Article 30 (1), Article 19 (1), and Article 23. General factors that affect the law enforcement process: Legal Factors, Law Enforcement Factors, Factors of Supporting Facilities or Facilities, Community Factors, and Cultural Factors.